Does the Addition of Cetuximab to Radiochemotherapy Improve Outcome of Patients with Locally Advanced Rectal Cancer? Long-Term Results from Phase II Trials. (15th March 2015) - Kripp, M.; Horisberger, K.; Mai, S.; Kienle, P.; Gaiser, T.; Post, S.; Wenz, F.; Merx, K.; Hofheinz, R.-D.
Abstract : Purpose . The addition of cetuximab to radiochemotherapy (RCT) failed to improve complete response rates in locally advanced rectal cancer (LARC). We report the long-term results in patients treated within two sequential clinical trials. Methods . Patients receiving neoadjuvant RCT using capecitabine and irinotecan (CapIri) within a phase I/II trial or CapIri + cetuximab within a phase II trial were evaluated for analysis of disease-free survival (DFS) and overall survival (OS). KRAS exon 2 mutational status had been analyzed in patients receiving cetuximab. Results . 37 patients from the CapIri trial and 49 patients from the CapIri-cetuximab treatment group were evaluable. Median follow-up time was 75.2 months. The 5-year DFS rate was 82% (CapIri) and 79% (CapIri-cetuximab) ( P = 0.62 ) . The median OS was 127.4 months. 5-year OS was 73% for both groups (CapIri and CapIri-cetuximab) ( P = 0.61 ) . No significant difference in DFS ( P = 0.86 ) or OS ( P = 0.39 ) was noticed between patients receiving CapIri and those receiving CapIri-cetuximab with KRAS wild-type tumors. Conclusions . As the addition of cetuximab did not improve neither DFS nor OS it should not play a role in the perioperative treatment of patients with LARC, not even of patients with (K)RAS WT tumors.